Klasterisasi Daerah Rawan Bencana Alam Menggunakan Algoritma K-Means - Michael Kevin Adinata; Ali Mahmudi; Yosep Agus Pranoto (Infotek: Jurnal Informatika dan Teknologi, 2025)
East Java is a province with high vulnerability to disasters, such as floods, landslides, earthquakes, and strong winds, which have an impact on material losses, casualties, and deterioration of socio-economic conditions, especially in rural areas. The lack of mitigation strategies and resource allocation worsens disaster management. This study aims to classify disaster data using the K-Means algorithm to overcome the limitations of descriptive analysis conducted by BPBD East Java. The data used includes 1125 disaster events with variable disaster frequency, total damage, and the number of casualties per sub-district in East Java districts and cities during 2021-2022, obtained from the official website of the East Java BPBD. The K-Means algorithm was chosen because of its efficiency in managing big data and its flexibility in cluster formation. The results of the study show that in 2021, the region in East Java is divided into three clusters based on the level of disaster risk: Cluster 1 (low risk) with 192 sub-districts, Cluster 2 (medium risk) with 35 sub-districts, and Cluster 3 (high risk) with 10 sub-districts. In 2022, significant changes were seen in Cluster 1, which includes 462 sub-districts, Cluster 2 with 20 sub-districts, and Cluster 3 with 11 sub-districts. The results of this study are expected to support the government's decision-making priorities, especially in disaster management and resource allocation based on risk levels